PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN DAN LOYALITAS KONSUMEN PADA KAFE KOPI KAMPUS JEMBER - Puspitasari, Ayu Tri; Nike Norma Epriliyana; Hermawan Teguh Saputra (Universitas Muhammadiyah Surakarta, 2025)
The rapid growth of business in Indonesia has led to increasingly intense market competition, including in Jember, where food and beverage businesses are on the rise. One such business is Kopi Kampus Café, established in 2022, which has attracted a diverse range of customers— from students and youth to the general local community. This study aims to analyze the influence of Experiential Marketing on customer satisfaction and loyalty at Kopi Kampus Jember. A quantitative approach was used, employing a survey design with data collected through questionnaires. The study involved 260 respondents who are customers of the café. The research instrument was designed to measure three key variables: Experiential Marketing, customer satisfaction, and customer loyalty. Data analysis techniques included instrument testing, path analysis, and hypothesis testing, with SPSS 27 as the supporting tool. The expected outcome of this research is to contribute to more effective marketing strategies, particularly within the student segment, and to provide insights for Kopi Kampus management on how to implement Experiential Marketing strategies to enhance customer satisfaction and loyalty.